European Respiratory Society International Congress 2017: highlights from the Clinical Assembly - Kahn, Nicolas; Mekov, Evgeni; Fregonese, Laura; Andrianopoulos, Vasileios; Franssen, Frits M. E.; Grgic, Aleksandar; Coolen, Johan; Bonta, Peter I.; Gompelmann, Daniela; Annema, Jouke T.; Faverio, Paola; Bonella, Francesco; et al. (ERJ Open Research, 2018)
This article contains highlights and a selection of the scientific advances from the European Respiratory Society's Clinical Assembly (Assembly 1 and its six respective groups) that were presented at the 2017 European Respiratory Society International Congress in Milan, Italy. The most relevant topics from each of the groups will be discussed, covering a wide range of areas including clinical problems, rehabilitation and chronic care, thoracic imaging, interventional pulmonology, diffuse and parenchymal lung diseases, and general practice and primary care. In this comprehensive review, the newest research and actual data as well as award-winning abstracts and highlight sessions will be discussed. - Tweetable abstract ERSpublications - click to tweetA highlights review of selected presentations from #ERSCongress 2017 by the @ERStalk Clinical Assembly http://ow.ly/p3fB30gSb24